2014
DOI: 10.1007/s11414-014-9397-8
|View full text |Cite
|
Sign up to set email alerts
|

Provider Experiences with Prison Care and Aftercare for Women with Co-occurring Mental Health and Substance Use Disorders: Treatment, Resource, and Systems Integration Challenges

Abstract: Incarcerated women with co-occurring mental health and substance use disorders (COD) face complex psychosocial challenges at community reentry. This study used qualitative methods to evaluate the perspectives of 14 prison and aftercare providers about service delivery challenges and treatment needs of reentering women with COD. Providers viewed the needs of women prisoners with COD as distinct from those of women with substance use alone and from men with COD. Providers described optimal aftercare for women wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
68
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(76 citation statements)
references
References 56 publications
(68 reference statements)
4
68
0
2
Order By: Relevance
“…Though some prior research suggests incarcerated women face substandard health care during their imprisonment – especially among pregnant and older women 54–56 – findings of this study align with previous studies that highlight the significant health care challenges continue when women re-enter the community. Specifically, though a greater percentage of women identify unfair treatment or discrimination and the health care system as barriers to accessing services while incarcerated, all other barriers examined are more likely to be cited by women while in the community.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Though some prior research suggests incarcerated women face substandard health care during their imprisonment – especially among pregnant and older women 54–56 – findings of this study align with previous studies that highlight the significant health care challenges continue when women re-enter the community. Specifically, though a greater percentage of women identify unfair treatment or discrimination and the health care system as barriers to accessing services while incarcerated, all other barriers examined are more likely to be cited by women while in the community.…”
Section: Discussionsupporting
confidence: 84%
“…57 This is the especially relevant for those who have co-occurring mental health and substance use disorders, for which the stress of re-entry may precipitate relapse and/or aggravate mental health problems. 56 Among those with infectious diseases, continuity of and compliance with prescribed treatment(s) are essential for maintaining individual and public health. For those who are HIV positive, for example, discontinuing anti-retroviral medications can result in drug resistance and increased viral load, making disease transmission more likely in the event that discordant HIV-status individuals engage in risk behaviors like unprotected sex.…”
Section: Discussionmentioning
confidence: 99%
“…Pilot work leading up to this study 22,29,4951 indicated that: (1) treatment for MDD is needed in prisons, (2) group IPT for MDD was likely effective among female prisoners and was feasible and acceptable to them and to their providers; (3) IPT’s interpersonal approach made sense to prisoners and prison stakeholders and seemed important to them; and (4) non-specialist bachelor’s level prison counselors can deliver IPT adherently and competently. These preliminary studies have prepared us to successfully conduct a large, multi-component treatment trial that takes place in many prisons across two states, and incorporate cost, medical and correctional record, stakeholder survey and interview, expert rater, and process note data.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Preliminary studies included two open trials 29,49 and a pilot randomized trial 22 of adaptations of IPT for women prisoners with MDD, as well as mixed method studies with study participants 50 and prison providers 51 about the treatment needs of prisoners with MDD. This research indicated that MDD treatment in prisons is needed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation